Photochemical Fluoroalkylations with Fluorinated Gases Facilitated by a Robust Metal–Organic Framework - He, Jiachen; Randrianandraina, Joharimanitra; Adamji, Husain; Chang, Valerie; Lai, Yihuan; Nguyen, Truong N.; Roman-Leshkov, Yuriy; Kulik, Heather J.; Lee, Jung-Hoon; Milner, Phillip J. (American Chemical Society, 2026)
Photochemistry has greatly advanced the sustainable synthesis of complex molecules, but its application for late-stage fluoroalkylation─crucial due to the presence of fluorine in >20% of pharmaceuticals and >65% of agrochemicals─is hindered by the poor atom economy of traditional fluoroalkylating agents. Herein, we demonstrate that simple fluorinated gases, which represent ideal building blocks for fluorochemical synthesis, can be stored within the robust, inexpensive, and redox-innocent metal–organic framework Al–fum to streamline the development of 11 photoinduced fluoroalkylation reactions, including bimolecular homolytic substitution (SH2), metallophotoredox cross-coupling, and [2+2] cycloaddition reactions. The gas–Al–fum reagents are prepared via simple gas-dosing procedures, stable for several months in a desiccator at room temperature, and are compatible with reaction optimization campaigns and mechanistic studies using precise quantities of gases. Overall, our findings provide a general platform for the utilization of inexpensive gaseous building blocks in photochemistry, paving the way for the sustainable synthesis of next-generation fluorochemicals.